Spitzer observations of large amplitude variables in the LMC and IC 1613 - Whitelock Patricia A.; Kasliwal Mansi; Boyer Martha (EPJ Web of Conferences, 2017)
The 3.6 and 4.5 ìm characteristics of asymptotic giant branch variables in the LMC and IC 1613 are discussed. For C-rich Mira variables there is a very clear periodluminosity-colour relation, where the [3.6] . [4.5] colour is associated with the amount of circumstellar material and correlated with the pulsation amplitude. The [4.5] periodluminosity relation for dusty stars is approximately one mag brighter than for their naked counterparts with comparable periods.